AKTIVITAS PEMBELAJARAN BAGI SANTRI USIA DINI BERBASIS MODERASI DAN TAZKIYATUN NAFS - Hasanah, Imroatul (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2023)
This article describes learning activities for early-age students based on moderation and tazkiyatun nafs at the Nurul Huda Mangunsari Islamic boarding school, Lumajang Regency. This research utilizes a qualitative approach to investigate aspects of the natural environment and attempts to interpret these phenomena. Data collection techniques utilized observation, interviews, and documentation studies. In this research, researchers used several stages of data analysis, namely the reduction stage, data presentation stage, making temporary conclusions, and verification activities. The results of the research concluded that learning activities for early-age students at the Nurul Huda Islamic Boarding School provide a basis for understanding wisdom in producing various experiences regarding the development of psychological maturity, which is formed collectively by the student community in processing their reasoning and heart life as well as cultivating wise knowledge, original values, and attitudes. Furthermore, the wira'i personality becomes a bulwark for the mental and emotional stability of the santri community.